(3GdNjds - (3nerYneQ Hf GdeKfi GdJjej HGdhdGA, GdHUQj, CHh YHjO GdfMhj,J (B209 (3g` s
(3ChdgG (B:s
(3MOKfG CHh jhSa GdCUHgGfi bGd MOKfG CHh YHjOI eYeQ Hf GdeKfi bGd de Jcf GdYQH ai GdLGgdjI JUhf TjFG ef CehGdgG hdG JcQeg UjGfJgG GdNjd hEcQGegG dgG , deGdge ajgG ef GdYR hGdLeGd s
(3BNQgG (B:s
(3hbGd eGdc Hf fhjQI GdjQHhYi (B: (3OhGjJg cd GdOhGA hROJg HPdkG ceG jYWi GdeMH GdehSY Je cJGH GdNjd ef JCdja CHj YHjOI hGdMeO ddg s
(3HBNQgG eWGdYI eDQNI ai (B1327 (3g`s
(3UaMI GdYfhGf ePgHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B309s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs